PEMBERIAN EDUKASI DALAM MENINGKATKAN UPAYA KUALITAS HIDUP PADA PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS MACCINI SAWAH - Fransiskawati Bawole; Andi Mappanganro; Tutik Agustini; Akbar Asfar (Jurnal Kesehatan, 2025)
Hypertension is a non-communicable disease that is a global health problem and a major risk factor for cardiovascular disease, kidney failure, and other serious complications. Hypertension management relies not only on drug therapy but also requires changes in behavior and a healthy lifestyle. Providing health education to patients is expected to improve understanding of the disease, medication adherence, and the adoption of a healthy lifestyle, thereby improving the quality of life of hypertensive patients. This study aimed to determine the effect of providing education on improving the quality of life of hypertensive patients in the Maccini Sawah Community Health Center work area. This study used a pre-experimental design with a pretest-posttest approach. Data collection methods used observation sheets and interviews. The study showed a significant decrease in systolic and diastolic blood pressure after the Education to Improve Quality of Life intervention, demonstrating the effectiveness of this technique in helping control blood pressure. Providing structured and ongoing education can improve the quality of life of hypertensive patients. It is hoped that healthcare workers will routinely provide education and facilitate patients in adopting healthy lifestyles to minimize the risk of hypertension complications.